2018
DOI: 10.1212/wnl.0000000000005261
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of neurofilament and phospho-tau/tau ratio in the frontotemporal dementia spectrum

Abstract: ObjectiveTo examine the clinical value of neurofilament light chain (NfL) and the phospho-tau/total tau ratio (p/t-tau) across the entire frontotemporal dementia (FTD) spectrum in a large, well-defined cohort.MethodsCSF NfL and p/t-tau levels were studied in 361 patients with FTD: 179 behavioral variant FTD, 17 FTD with motor neuron disease (FTD-MND), 36 semantic variant primary progressive aphasia (PPA), 19 nonfluent variant PPA, 4 logopenic variant PPA (lvPPA), 42 corticobasal syndrome, and 64 progressive su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 102 publications
(136 citation statements)
references
References 42 publications
9
121
2
4
Order By: Relevance
“…Patients with high NfL experienced the steepest annual decline in both clinical rating scales and MRI measurements. These findings are consistent with previous studies establishing the prognostic value of both CSF7, 8, 36 and plasma7, 9 NfL in genetic FTD syndromes. Within our bvFTD and nfvPPA cohorts, median CSF NfL levels (4.1 × 10 3  pg/mL and 5.17 × 10 3  pg/mL, respectively) separated patients into subgroups with clinically significant annual change and clinically negligible annual change.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Patients with high NfL experienced the steepest annual decline in both clinical rating scales and MRI measurements. These findings are consistent with previous studies establishing the prognostic value of both CSF7, 8, 36 and plasma7, 9 NfL in genetic FTD syndromes. Within our bvFTD and nfvPPA cohorts, median CSF NfL levels (4.1 × 10 3  pg/mL and 5.17 × 10 3  pg/mL, respectively) separated patients into subgroups with clinically significant annual change and clinically negligible annual change.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, our findings may reflect the pathogenicity of early comorbid A β 1‐42 deposition in FTD, preceding frank biomarker‐positive Alzheimer's disease. Consistent with previous studies,36, 37 patients with FTLD‐TDP had relatively low p‐tau/t‐tau ratios compared to patients with FTLD‐tau, and a cutoff ratio of 0.29 gave modest sensitivity and specificity in detecting FTLD‐TDP en vivo. It should be noted that our FTLD‐TDP and FTLD‐tau cohorts did not include patients with svPPA (due to the limitations of our data), and our FTLD‐TDP cohort had a high burden of motor neuron disease.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Using a subset of cases for which NfL measurements were available (FTLD = 92, CON = 28), we observed that the FTLD vs. CON model (AUC:0.94; P  < 0.0001) performed similar to NfL alone (AUC:0.94 P  < 0.0001, Fig. S3), a non‐disease specific marker that optimally discriminate FTLD cases from controls 27, 32, 33, 34…”
Section: Resultsmentioning
confidence: 90%
“…The levels of AD‐related biomarkers (total and phosphorylated tau [t‐Tau and pTau 181 ]) were analyzed in the corresponding sample collection center using the commercially available kits (Emory: INNO‐BIA AlzBio3; Milan: Innotest A β (1‐42), hTAUAg, phosphor‐Tau(181P); Fujiribo, Ghent, Belgium, both using the same antibodies) as previously described 9, 26. The levels of neurofilament light change (NfL) were measured in a subset of cases within the validation cohort using a validated immunoassay ELISA of UmanDiagnostics (Umeå, Sweden) as previously described 27. All biomarkers were analyzed by a single experienced technician blinded to the clinical groups.…”
Section: Methodsmentioning
confidence: 99%